2009
DOI: 10.1016/j.ijporl.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The development of sleep disordered breathing from 4 to 12 years and dental arch morphology

Abstract: Objective: To track the development of sleep disordered breathing (SDB) as well as dentofacial morphology in cohort of children by having them complete a questionaire at ages 4, 6 and 12 . Clinical examination, sleep studies (at ages 4 and 12) and orthodontic evaluation were carried out on all who were reported to snore regularly and children who did not snore at all. Results: Out of the original group of 615 children, 64% (393) answered the inquiry on all three occasions. Of those, 27 snored regularly and 231… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 23 publications
2
28
1
1
Order By: Relevance
“…There were no significant gender differences in the incidence rates of these diagnoses in offspring with a parent affected with OSAS, which can be explained by the relatively fewer numbers of patients in this subgroup than in the entire population The categorization into different age groups in the present study showed that the highest incidence of SDB is in the group below 8 years. Other studies have shown similar results with a higher frequency of SDB in younger children [14]. In the present study, family income was investigated as an indicator of socioeconomic position.…”
Section: Discussionsupporting
confidence: 69%
“…There were no significant gender differences in the incidence rates of these diagnoses in offspring with a parent affected with OSAS, which can be explained by the relatively fewer numbers of patients in this subgroup than in the entire population The categorization into different age groups in the present study showed that the highest incidence of SDB is in the group below 8 years. Other studies have shown similar results with a higher frequency of SDB in younger children [14]. In the present study, family income was investigated as an indicator of socioeconomic position.…”
Section: Discussionsupporting
confidence: 69%
“…e) Persistent, untreated tonsillar hypertrophy and a narrow mandible predict persistent SDB (class III) [128,129].…”
Section: Literature Review A)mentioning
confidence: 99%
“…Five hundred and nine children took part in this first follow-up and were again contacted six years later to participate in a second follow-up at age twelve. Three hundred and ninety three children participated in all three examinations [11][12][13].…”
Section: Subjectsmentioning
confidence: 99%
“…In the two follow up studies at six and twelve years, they underwent new clinical ENT examinations. Those cases that were also snoring every night at age 12 were given a second sleep polygraphy as were six of the not-snoring controls [13].…”
Section: Ent and Sleep Examinationsmentioning
confidence: 99%
See 1 more Smart Citation